Institutional Mechanisms of International Judicial Cooperation in Combating Doping in Sports - YANISHEVSKAYA, Yana Andreevna (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The fight against doping at the legislative level began in 1989 as a result ofthe adoption of the Anti-Doping Convention, signed in Strasbourg. Relevance. The relevance of the study is determined, firstly, by the ongoing scientific discussion and lack of consensus on the nature and role of institutional mechanisms of international judicial cooperation in combating doping in modern sports and, secondly, by the identification of the problems and substantiation of the ways of solving them in relation to increasing effectiveness of combating doping in sports. Aim. The aim of the article is to develop a functional and legal method that would determine the effectiveness of institutional mechanisms of international judicial cooperation in combating doping in sports. Methods. The basic method of the study is the deductive method, allowing to study the nature of institutional mechanisms of international judicial cooperation in combating doping in sports. The main method of the problem solution is the study of the regulatory framework for the implementation of the main provisions of international legal acts regulating the fight against doping. Results. The article proves the theoretical pendency of the problem of the implementation of institutional mechanisms of international judicial cooperation in combating doping in sports. The practical significance of the obtained results is associated with the fact that national anti-doping organizations should develop national anti-doping rules and international federations should develop their anti-doping rules.